The woman who discovered printing - Barrett, T. H. (Yale University Press, 2008)
"T. H. Barrett, a leading scholar of medieval China, brings us the answers through the intriguing story of Empress Wu (AD 625-705) and the revolution in printing that occurred during her rule. Linking Asian and European history with substantial new research into Chinese sources, Barrett identifies methods of transmitting texts before printing and explains the historical context of seventh-century China. He explores the dynastic reasons behind Empress Wu's specific interest in printing and the motivating role of her private religious beliefs. He also deduces from eighth- and ninth-century Chinese records an explanation for the lesser impact of the introduction of printing in China than in Europe. As Renaissance Europe was later astonished to learn of China's achievement, so today's reader will be fascinated by this engaging perspective on the history of printing and the technological superiority of Empress Wu's China"--Publisher's description